Plummer-Vinson Syndrome – A Community-Based Case Study - Priyadharishini, Joy; L, Liza (Indian Journal of Nursing Sciences, 2024)
Plummer-Vinson syndrome (PVS) is a rare syndrome mostly affecting women, which is mainly due to dietary deficiencies. Health education and health promotion are the key in prevention of this syndrome. Systematic history collection and physical examination will help the health-care provider to detect the syndrome and start treatment at the earliest. Negligence of the disease or mismanagement might lead to devastating complications. The condition has been reported most commonly in thin-built, middle-aged, and American women. The esophageal webs in PVS are thin mucosal folds, which are best seen either in lateral views at barium swallow or at esophagoscopy. These are usually semilunar or crescentic, being located most often along the anterior esophageal wall, but can be concentric. The exact cause and pathogenesis of PVS remain unclear, though iron and other nutritional deficiencies, genetic predisposition, and autoimmunity have all been implicated in formation of the webs. Treatment includes correction of iron deficiency and endoscopic dilation of the esophageal webs to relieve dysphagia. PVS is associated with an increased risk of hypopharyngeal and esophageal malignancies. Correction of iron deficiency may arrest and reverse the mucosal changes and possibly reduces this risk. This article discusses on the etiology, clinical manifestations, investigations, management, and complications of PVS. Primary health-care professionals have a greater role in primary prevention and early detection of this syndrome thereby manages the symptoms well.